The Updating of the Nautical Chart Number 69 on Java Sea Area for Safety Navigation of Sailing - Dwi Septri Hastuti; Bambang Kun Cahyono (Jurnal Geospasial Indonesia, 2019)
Indonesia is the largest archipelagic country in the world that has become one of the main routes in international marine trade by contributing 40% of all international marine trade routes. The importance of waterways in international trading demands the existence of nautical chart for navigation. Time after time, the sea changes, therefore nautical chart needs to be update especially on the area that has a high marine traffic density such as Java Sea which currently has developed an electronic map for navigation, however paper charts are still needed for planning shipping line, the navigation on small boats and backup of charts on large ships. The aim to be achieved from this research is the availability of the latest paper chart which is appropriate with IHO standard S-4, INT1 (symbols, abbreviations and terms used on charts), INT2 (the boundary lines, gradient, grid and linear scale) and Chart Number 1. Updating chart number 69 was created by using data Electronic Navigation Chart (ENC)  Northen part of Central Java region, data raster paper chart number 69  the ninth edition of the second expenditure, survey data 2017 in Cirebon and the Eastern part of Java Sea and Indonesian Notice to Mariners number 11-29 year 2017. Data obtained from the Pusat Hidrografi dan Oseanografi TNI-AL. The software used in production of nautical chart is Paper Chart Composer (PCC). Then it was added the updated data and information to the chart. The result of production a chart were corrected using digital and manual quality control analysis to eliminate errors in the process of production chart. As a result of updating nautical chart number 69 is that some of the objects that had been corrected have errors so it needs to be repaired until no more errors occur. The updating paper chart was already matched to standard IHO S-4 and INT1. The visualization of paper chart in accordance with the standard IHO INT2 and Chart number 1. The avaibility of paper chart number 69 with the update of data on the area of the Java Sea has been accomplished and can be used by mariner to navigation.